Nablus syndrome: Easy to diagnose yet difficult to solve. Issue 4 (22nd December 2018) - Allanson, Judith; Smith, Amanda; Forzano, Francesca; Lin, Angela E.; Raas‐Rothschild, Annick; Howley, Heather E.; Boycott, Kym M.
Abstract: Nablus syndrome was first described by the late Ahmad Teebi in 2000, and 13 individuals have been reported to date. Nablus syndrome can be clinically diagnosed based on striking facial features, including tight glistening skin with reduced facial expression, blepharophimosis, telecanthus, bulky nasal tip, abnormal external ear architecture, upswept frontal hairline, and sparse eyebrows. However, the precise genetic etiology for this rare condition remains elusive. Comparative microarray analyses of individuals with Nablus syndrome (including two mother–son pairs) reveal an overlapping 8q22.1 microdeletion, with a minimal critical region of 1.84 Mb (94.43–96.27 Mb). Whereas this deletion is present in all affected individuals, 13 individuals without Nablus syndrome (including two mother–child pairs) also have the 8q22.1 microdeletion that partially or fully overlaps the minimal critical region. Thus, the 8q22.1 microdeletion is necessary but not sufficient to cause the clinical features characteristic of Nablus syndrome. We discuss possible explanations for Nablus syndrome, including one‐locus, two‐locus, epigenetic, and environmental mechanisms. We performed exome sequencing for five individuals with Nablus syndrome. Although we failed to identify any deleterious rare coding variants in the critical region that were shared between individuals, we did identify one common SNP in an intronic region that was shared. Clearly, unraveling the genetic mechanism(s) of Nablus syndrome will require additional investigation, including genomic and RNA sequencing of a larger cohort of affected individuals. If successful, it will provide important insights into fundamental concepts such as variable expressivity, incomplete penetrance, and complex disease relevant to both Mendelian and non‐Mendelian disorders.